ปัจจัยที่เกี่ยวข้องกับภาวะความดันโลหิตสูงในประชาชนที่อาศัยอยู่เขตพื้นที่แนวชายแดนไทย-พม่า จังหวัดแม่ฮ่องสอน - หัสดิน สติปัญญาเลิศ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this descriptive study was to examine the prevalence and factors related to hypertension among people living in the area of Thai–Myanmar borderline, Mae Hong Son province. The data were collected from information of 3,280 people who came for hypertension screening by using a screening questionnaire at local Sub - District Health Promotion Hospitals (SDHPH) in 2013. The questionnaire comprised data related to personal information, health status and risk behavior. Descriptive statistics and Prevalence Ratio were used for data analysis. The finding of this study indicated that overall prevalence of hypertension among sample was 24.5 %. Prevalence of Pa Bong, Mok Jam Pae, Nai Soi and Na Pla Jaad Sub District Health Promotion Hospitals were 28.7%, 20.9%, 20.6% and 18.6% respectively. Personal information factor which significantly associated to hypertension were age, sex, nationality, community and family history related to chronic diseases (p < .05). The result indicated that people aged above 40 years had 3.5 times higher risk than those who aged below 40 years (PR = 3.5, p < .001). Female had 1.3 time higher risk than male (PR = 1.3, p< .001). Thai nationality had 1.3 times higher risk than other nationalities (PR = 1.3, p < .05). People living in the southern part of Mae Hong Son had 1.3 times higher risk than those who live in northern part (1.3, p< .001). People who had families with history of hypertension had 1.8 times higher risk than those with family without history of hypertension (PR = 1.8, p< .001). Risk factors related to health status which significantly associated with hypertension were Body Mass Index (BMI), waist line, level of blood sugar and complication of diseases (p < .05). The result found that people who categorized as obesity according to BMI calculation and had 1.5 times higher risk that people with normal result (PR = 1.5, p< .001). Male and female with standard waist line had 2.3 and 1.7 times higher risk than normal result respectively (PR = 2.3, p < .001; PR = 1.7, p < .001). People with high level of blood sugar had 1.9 time higher risk than normal people (PR = 1.9, p< .001) and people with complication of diseases had 2.9 time higher risk than those who did not have any complication of disease (PR = 2.9, p< .001). Behaviors factors with significantly association to hypertension were smoking and drinking alcohol (p < .05). The result reported that those who smoke and drink alcohol had 1.2 time higher risk to hypertension than those who do not smoke and drink alcohol (p< .05). Health providers should continue emphasizing on surveillance of hypertension and risk factor control among the population in order to decrease the incidence of hypertension.